Integrating Vegetables into Maize-Based Systems for Enhanced Nutrition and Income Generation: Scoping Study by AVRDC - World Vegetable Center (International Food Policy Research Institute, 2015)
We conduct a scoping study to establish determinant sociological, infrastructural, biological, and agronomic factors that currently affect vegetable production and offer scope for future vegetable production in the study area. Project title: Research in Sustainable Intensification in the Sub-Humid Maize-Based Cropping Systems of Babati, Tanzania Project abstract: Scoping study to assess current status and future potential, increase awareness and develop partnerships for action research, technology development, and capacity building. Project website: http://africa-rising.net